Comment on “Resolving the Tropical Pacific/Atlantic Interaction Conundrum” by Feng Jiang et al. (2023) - Ingo Richter; Noel Keenlyside; Tomoki Tozuka; Yuko Okumura; Chunzai Wang; Ping Chang; Shoichiro Kido; Hiroki Tokinaga (Geophysical Research Letters)
Abstract Jiang et al. (2023), https://doi.org/10.1029/2023gl103777 argue that the apparent impact of the equatorial Atlantic on El Niño‐Southern Oscillation (ENSO) is a statistical artifact, and that the 6‐month lead correlation reported in previous studies stems from early developing ENSO events driving the equatorial Atlantic zonal mode (AZM) in boreal summer and maturing in winter. Closer examination, however, reveals that most AZM events develop too early to be driven by developing ENSO, and that the influence of decaying ENSO events has to be considered too. Thus, while early developing ENSO events may play a role, they do not fully explain observed AZM behavior. Our aim is not to argue for or against an AZM influence on ENSO, but rather to show that Jiang et al.’s analysis is insufficient to resolve this issue. More analysis will be needed for a deeper understanding of Atlantic‐Pacific interaction.